Analysis of recovery methods` efficacy applied up to 72 hours postmatch in professional football: a systematic review with graded recommendations - Querido, S. M.; Radaelli, R.; Brito, J.; Vaz, J. R.; Freitas, S. R. (International Journal of Sports Physiology and Performance, 2022)
Background: Sleep, nutrition, active recovery, cold-water immersion, and massage were recently reported as the most used postmatch recovery methods in professional football. However, the recommendations concerning the effect of these methods remain unclear. Purpose: To systematically review the literature regarding the effectiveness of the most common recovery methods applied to male and female football players (or other team sports) 72 hours postmatches and to provide graded recommendations for their use. Methods: A systematic search of the literature was performed, and the level of evidence of randomized and nonrandomized studies was classified as 1 or 2, respectively, with additional ++, +, and - classification according to the quality of the study and risk of bias. Graded recommendations were provided regarding the effectiveness of recovery methods for physical, physiological, and perceptive variables. Results: From the 3472 articles identified, 39 met the inclusion criteria for analysis. The studies` levels of evidence varied among methods (sleep: 2+ to 1++; nutrition: 2- to 1+; cold-water immersion: 2- to 1++; active recovery: 2- to 1+; and massage: 1- to 1+). Different graded recommendations were attributed, and none of them favored the effective use of recovery methods for physiological and physical parameters, whereas massage and cold-water immersion were recommended as beneficial for perceptive variables. Conclusions: Cold-water immersion and massage can be recommended to recover up to 72 hours postmatch at a perceptive level. However, there is a current need for high-quality research that identifies effective recovery strategies that enhance recovery at the physical and physiological levels.